IBM PENELITIAN TINDAKAN KELAS GURU SD NEGERI 101868 DAN SDN 105323 DESA BAKARAN BATU KABUPATEN DELI SERDANG MELALUI PENDAMPINGAN PENGEMBANGAN KEPROFESIAN BERKELANJUTAN - Djulia, Ely; Simatupang, Halim; Nurhairani, Nurhairani; Amrizal, Amrizal (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This study was conducted by delivering 8-day action research workshop, followed up by mentoring into each group during teacher doing action research focusing on designing action research proposal, wrting their action research report, and wrting report into scientific article,,facilitating teacher to publish their article into journal at  LPM Unimed or journal with  ISSN.This study was conducted at two partner schools:  SD Negeri 101868 Desa Sena Kecamatan Batang Kuis and  SD Negeri 105323 Desa Bakaran Batu Kecamatan Batang Kuis Kabupaten Deli Serdang. The outcome of this  IbM is Primary teachers understand principle and procedure of action research, teachers are able to design and write action research proposal, conduct action research, from planning, action, observation, until  reflection, reporting result of action research and publish them into scientific journal. The output of this IbM is product of action research reports and scientific articles, hopefully they can be published. Key Word: Action Research Workshop, Teaching Learning Innovation